1989
DOI: 10.1097/00006842-198901000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual cycle abnormalities and subclinical eating disorders: a preliminary report.

Abstract: Menstrual dysfunction is a common concomitant of anorexia nervosa and bulimia. Initial investigations emphasized the role of weight loss and lean/fat ratio in amenorrhea. Subsequent studies suggest a more complex interaction between eating disorders and menstrual status. However, in past investigations, menstrual abnormalities have been confounded with low weight. We conducted two studies to ascertain the prevalence of menstrual abnormalities in a group of women with subclinical eating pathology versus an age-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 10 publications
(6 reference statements)
0
11
0
1
Order By: Relevance
“…For instance, Kreipe et al reported menstrual dysfunction in college undergraduates with partial ED. In their study, 93% to 100% of these subjects reported a history of abnormal menstrual cycles [100]. Two other studies among adolescents reported similar associations between partial ED and amenorrhea, with no significant association with body mass index [78,101].…”
Section: Somatic Co-morbidities Of Partial Edmentioning
confidence: 70%
“…For instance, Kreipe et al reported menstrual dysfunction in college undergraduates with partial ED. In their study, 93% to 100% of these subjects reported a history of abnormal menstrual cycles [100]. Two other studies among adolescents reported similar associations between partial ED and amenorrhea, with no significant association with body mass index [78,101].…”
Section: Somatic Co-morbidities Of Partial Edmentioning
confidence: 70%
“…Other studies have shown that amenorrhea did not discriminate between women with AN and women who met all diagnostic criteria except amenorrhea across a number of relevant variables such as demographics, illness characteristics, psychiatric comorbidity, and family history. 3,14,15,[33][34][35][36] The most relevant factors associated with menstrual dysfunction measured in this study were BMI, recalled caloric intake, and levels of exercise. Lifetime minimum BMI was significantly associated with amenorrhea as participants with primary amenorrhea reported the lowest maximum lifetime BMI and the lowest minimum lifetime BMI of all menstrual status groups.…”
Section: Resultsmentioning
confidence: 92%
“…These studies focused on samples comprising individuals with broader definitions of AN and included women meeting all the diagnostic criteria of AN except amenorrhea (partial syndrome AN). 3,14,15,[33][34][35][36] Women with amenorrhea had a significantly lower body mass index (BMI) than those without amenorrhea. 33,36 In contrast, Garfinkel et al 3 observed that the degree of weight loss was similar in women with and without amenorrhea.…”
Section: Introductionmentioning
confidence: 99%
“…Other nutritional deficiencies, such as iron deficiency, can be associated with growth decrease and anaemia in adolescents (Dietz & Hartung, 1985). Additionally, adopting unbalanced eating habits has been connected with menstrual irregularity or amenorrhea (Kreipe, Strauss, Hodgman, & Ryan, 1989). Table 5 summarises the most popular fad diets, their main components and their physiological implications, the main of which are explained below.…”
Section: Health Consequences Of Fad Dietingmentioning
confidence: 99%